Uji Efektivitas Daun Sirih Merah (Piper crocatum) Terhadap Penurunan Kadar Gula Darah Mencit Putih Jantan (Mus musculus) yang Diinduksi Aloksan - Andriani, Medi; Putra, Rizki Yulion; Rosyta, Dini Galoh (BIOEDUSCIENCE, 2024)
Background: Hyperglycemia is when blood sugar levels increase excessively from normal sugar levels. High blood sugar levels in the body that exceed normal limits occur when the random blood sugar test value is ≥200 mg/dl and fasting blood sugar is ≥126 mg/dl. One natural ingredient known to lower blood sugar levels is red betel leaf (Piper crocatum). Methods: The method used in this research is the extraction and fractionation of n-hexane, ethyl acetate fraction, n-butanol fraction, and residual water fraction. Results: The results of research that has been carried out by giving fractionated n-butanol is effective in reducing blood sugar levels in male white mice (Mus musculus) that have been induced by alloxan. Conclusions: The positive group was obtained, and the results of administering the n-butanol fraction at a dose of 100 mg/KgBW affected reducing the blood sugar levels of male mice (Mus musculus) which had been induced by alloxan on days 2, 4, and 6, which decreased the most.